In Vitro Regeneration of Phyllanthus amarus Schum. and Thonn.: An Important Medicinal Plant - Sen, A.; Sharma, M.M.; Grover, D.; Batra, A. (Our Nature, 2010)
An efficient in vitro plant regeneration protocol was developed for the medicinally potent plant species Phyllanthus amarus Schum. and Thonn. (Euphorbiaceae) using nodal segment as explant. Maximum multiplication of shoots (15.275±0.96) was achieved on Murashige and Skoog’s medium supplemented with BAP (0.5 mg/l) after 3-4 weeks of inoculation. The shoots were separated from cluster and subcultured for their elongation on the same medium. In vitro flowering was also observed on the elongated shoots after 3–4 weeks of sub culturing on the shoot elongation medium. In vitro rooting was obtained on half strength MS medium supplemented with IBA (0.5 mg/l). Regenerated plants were successfully hardened and acclimatized, 80 % of plantlets survived well under natural conditions after transplantation. Key words: In vitro regeneration, multiple shoots, nodal segments, Phyllanthus amarus DOI: 10.3126/on.v7i1.2557 Our Nature (2009) 7:110-115